1995
DOI: 10.1007/bf02515762
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality and vertical structure of light‐attracted insect communities in a dipterocarp forest in Sarawak

Abstract: Nocturnal flying insects were collected monthly for 13 months using ultra violet light-traps set at various vertical levels in a weakly-seasonal, tropical lowland dipterocarp forest in Sarawak, Malaysia. Abundance, faunal composition, size distribution and guild structure of these samples were analyzed with respect to temporal and vertical distributions. The nocturnal flying insect community in the canopy level was highly dominated by fig wasps (84~) in individual number, and by scarabaeid beetles (28%) in wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
2
12

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(132 citation statements)
references
References 39 publications
9
109
2
12
Order By: Relevance
“…Studying upper-canopy leaves from across the Amazon Basin, Fyllas et al (2009) also observed significant variations in foliar carbon content, relating this to variations in M A and the extent of investment in constitutive defenses. Consistent with this and the observed positive vertical gradient in [C] DW both between and within trees is the tendency for leaves higher up rain forest canopies to have greater levels of carbon based defense compounds (Lowman and Box, 1983;Downum et al, 2001;Dominy et al, 2003), this perhaps being associated with higher abundances of herbivores such as insects and other arthropods also occurring there (Sutton, 1989;Kato et al, 1995;Koike et al, 1998;Basset et al, 2001).…”
Section: Gradients In Carbon and Cation Concentrationsmentioning
confidence: 72%
“…Studying upper-canopy leaves from across the Amazon Basin, Fyllas et al (2009) also observed significant variations in foliar carbon content, relating this to variations in M A and the extent of investment in constitutive defenses. Consistent with this and the observed positive vertical gradient in [C] DW both between and within trees is the tendency for leaves higher up rain forest canopies to have greater levels of carbon based defense compounds (Lowman and Box, 1983;Downum et al, 2001;Dominy et al, 2003), this perhaps being associated with higher abundances of herbivores such as insects and other arthropods also occurring there (Sutton, 1989;Kato et al, 1995;Koike et al, 1998;Basset et al, 2001).…”
Section: Gradients In Carbon and Cation Concentrationsmentioning
confidence: 72%
“…While there has been work on vertical strati¢cation in insect activity in tropical forests (e.g. Sutton et al 1983;Hammond 1990;Kato et al 1995;Wolda et al 1998), this has rarely been incorporated into studies of disturbance (but see DeVries et al 1997). This is a critical omission for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…These differences are likely to be determined by a range of factors including resource availability, microclimate preferences and predator avoidance (Haddow et al 1961;Kato et al 1995;Brü hl et al 1998;Rogers & Kitching 1998;Schultze et al 2001;Tanabe 2002;Basset et al 2003). The degree of specialization to resources and physiological tolerances to microclimate are, therefore, likely to be particularly important in structuring arthropod assemblage differences between the canopy and the ground.…”
Section: Introductionmentioning
confidence: 99%